1994
DOI: 10.1007/bf00017624
|View full text |Cite
|
Sign up to set email alerts
|

Energy metabolism of Chironomus anthracinus (Diptera: Chironomidae) from the profundal zone of Lake Esrom, Denmark, as a function of body size, temperature and oxygen concentration

Abstract: The profundal zone of Lake Esrom, Denmark has a dense population of Chironomus anthracinus, which survives 2-4 months of oxygen depletion each summer during stratification . The metabolism of 3rd and 4th instar larvae was examined in regard to variation in biomass and temperature . Respiration at air saturation was described by a curvilinear multiple regression relating oxygen consumption to individual AFDW and temperature . At 10 °C and varying oxygen regimes the 02 consumption and CO2 production of 4th insta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 6 publications
1
29
0
1
Order By: Relevance
“…The respiratory rate (R) trend we measured is in accordance with that one observed by Hamburger et al (1994) and Brodersen et al (2008) in other Chironomini such as C. anthracinus, C. riparius and C. hyperboreus Staeger 1845. Nevertheless a slight (not significant) increase in the first hours of treatment resembling typical a oxy-stressor, R remained constant within the first 24 h of treatment with a significant decrease only below 50% of oxygen saturation suggesting for C. riparius larvae from the Rio Gola a oxy-regulator behaviour (i.e., it regulates and maintains a constant R within a % saturation interval) (Brodersen et al, 2008).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The respiratory rate (R) trend we measured is in accordance with that one observed by Hamburger et al (1994) and Brodersen et al (2008) in other Chironomini such as C. anthracinus, C. riparius and C. hyperboreus Staeger 1845. Nevertheless a slight (not significant) increase in the first hours of treatment resembling typical a oxy-stressor, R remained constant within the first 24 h of treatment with a significant decrease only below 50% of oxygen saturation suggesting for C. riparius larvae from the Rio Gola a oxy-regulator behaviour (i.e., it regulates and maintains a constant R within a % saturation interval) (Brodersen et al, 2008).…”
Section: Discussionsupporting
confidence: 90%
“…larvae is covered by the alcoholic fermentation of glycogen stores to ethanol (Scholz and Zerbst-Boroffka, 1998). Hamburger et al (1994) reported that anaerobic metabolism represents from 3 (at 3 mgO 2 L -1 ) to 40% (at 0.5 mgO 2 L -1 ) of total energy production in Chironomus larvae (C. anthracinus can regulate its respiratory metabolism down to 2-3 mgO 2 L -1 ). Choi et al (2001) reported that at 1.6 mgO 2 L -1 a switch from aerobic to partial anaerobic metabolism occurred after 48 h of treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Short term studies have shown that the respiratory metabolism declines sharply below this level but is accompanied by increased anaerobic degradation of glycogen . The compensation for the loss in aerobic metabolism by anaerobic processes, however, is extremely small (Berg et al, 1962 ;Bairlein, 1989 ;Hamburger et al, 1994) .…”
Section: Introductionmentioning
confidence: 99%
“…Determinados gêneros apresentam adaptações que lhes permitem suportar condições de hipoxia e até de anóxia (HECKMAN, 1998;HAMBURGER et al, 1994). No entanto, mesmo representantes de tais gêneros acabam não suportando as baixas tensões de oxigênio se estas condições persistirem por muitos dias, como ocorre na "decoada".…”
Section: Um Dos Fatores Decisivos Para Os Baixíssimos Valores De Densunclassified